Active operations of Ashgabat branch of Russian-Asian Commercial Bank (1905–1917) - B. A. Alimdjanov (Омский научный вестник: Серия "Общество. История. Современность")
The topic of the history of banks’ activity in Central Asia has been little studied in national and world historiography, although its study allows revealing new aspects of the economic policy of the Russian Empire in the region. The article is written on the basis of documents extracted from the Russian State Historical Archives (RSHA). The financial institutions of the Russian Empire took into account local specifics and encouraged the production of export-oriented products. The main goal of the article is to reveal the active operations of the Russian-Asian Commercial Bank in the formation of market relations in the traditional economy of the outskirts of the Russian Empire. We believe that the colonial economy had a specific character, which was expressed not in the destruction of the local «industry», but in the development of agriculture. In writing the article, statistical methods and the theory of modernization of the colonial periphery were used